From personality to passion: The role of the Big Five factors. (1st February 2019) - Dalpé, Julien; Demers, Martin; Verner-Filion, Jérémie; Vallerand, Robert J.
Abstract: The present research investigated the role of the personality traits and facets of the Big Five Model in harmonious (HP) and obsessive (OP) passion. A total of 284 participants completed an online questionnaire measuring personality traits and facets, HP and OP, and positive and negative affect. Results from correlational and structural equation modeling analyses revealed that the conscientiousness, openness to experience, agreeableness, and extraversion traits (and most of their facets) were positively related to HP, while neuroticism, agreeableness, and extraversion (and most of their facets) were positively associated with OP. In turn, HP was positively related to positive affect and negatively related to negative affect. In contrast, OP was positively associated with negative affect. The results suggest that broad personality factors such as the Big Five and their facets play a role in the development of HP and OP.